COMMERCIAL MUSIC (POP CULTURE) STYLES AS THE MAIN MUSICAL SOURCE OF PRESERVATION OF ENDANGERED LANGUAGES IN A GLOBAL CONTEXT - Leon Gilberto Medellin Lopez (Proceeding IICACS, 2019)
Nowadays, the acknowledge of the big amount of endangered languages around the globe is still increasing while the preservation of them still in question due to the lack or the harm of linguistic policies as well, the hegemony of national languages that, in order to establish a more standardised national linguistic paradigm pushes the minority/native language into a state of emergency in its preservation. In the age of information and globalisation, different media has been utilised in order to promote the preservation of endangered languages, among them, publications in different areas like science, humanities and literature. Besides that, music has been also playing an important part in this terms due to its popularity and its social impact. In this paper will be focused in the commercial/pop culture music and its musical, linguistic and social implications since most of this musical expression are evidently considered as alien to the musical tradition in each case and paradoxically at the same time promoting the preservation of an endangered native language since this last one is considered a fundamental part of the traditional identity of each society.Keywords: Endangered Languages, Native languages, Languages national policies, Language preservation; Rap/Hip-hop Music; Globalization, Americas, Asia, Europe, Africa